Le « Roman des bêtes » : petit traité de mésologie et d’anthropologie ? - Sylvie Dardaillon; Christophe Meunier (Strenae)
The educational discourse of the picturebooks in the “Roman des bêtes” collection is ontological, biological, anthropological as much as ethological. While the images by Rojankovsky, May Angeli, Hélène Fatou and Marie Tenaille seek naturalistic precision, the texts by Lida, Christian Boutin and Roger Turc anthropomorphize the animal. The animal, a character in its own right, feels emotions and has interpersonal relationships with the members of its family. As the pages turn, we see them grow up, become adults and sometimes die. It is this connection between the animal kingdom and human societies that will be explored in this article. In the years 1910-1920, human geography emerges in France. It proposes a methodology that looked successively at people, their homes and their habitats. It is this same interlocking of scales that we find in the structuring of the narrative in the Père Castor’s picturebooks. The work of the German biologist von Uexküll in the 1920s highlights the close relationship that animals can have with their environment (habitat). These are relationships of give-and-take. Here again, the interdependence of animals is recurrent in the picturebooks, mirroring the human habitat.